Public speaking. Program 2, Dynamic delivery - Standard Deviants (Performing group); Cerebellum Corporation ([S.l.] : Cerebellum Corp., 2004)
The Standard Deviants show how to grab an audience's attention and bring them to their feet.
The Standard Deviants.
DVD.
Keywords: Public speaking; Instructional films